Evaluating Delayed Climate Policy by Cost-Risk Analysis - Robert Roth; Delf Neubersch; Hermann Held (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2020)
Cost-Risk Analysis (CRA) is a method to mathematically deduce preferences in line with a climate target. CRA is a trade-off, where costs of mitigating greenhouse gas emissions are weighted against the risk of exceeding climate targets. CRA enables a community supporting climate targets to evaluate delayed climate policy with an arbitrary length because the scope of CRA is not restricted to solutions that do not violate the target. For the first time we apply this approach to the problem of delayed climate policy using the integrated assessment model MIND-L. The most important results of our analysis are: (i) Using the most conservative risk metric welfare losses double for a 40 year delay of climate policy, that initially aims at limiting global mean temperature rise to 2 °C with a probability of 66%. (ii) The welfare losses are only driven by an increase in temperature. Mitigation costs are even decreasing, which can be seen as an incentive to delay mitigation efforts for decision makers who ignore risk. (iii) For the 2°C target, we find that maximum mitigation is optimal for any delay scenario beyond 2020, in line with previous studies using other approaches.
Keywords: 330; Klimapolitik; Kostenmanagement; Risikomanagement; Kosten-Nutzen-Analyse; Szenariotechnik